Refugee microenterprises: prospects and challenges - Kachkar, Omar; Mohammed, Mustafa Omar; Md Saad, Norma; Kayadibi, Saim (Journal of Asian and African Social Science and Humanities, 2016)
Economic engagement of refugees and supporting their micro enterprises have been acknowledged long ago by UNHCR and humanitarian agencies as an effective solution to promote self-sufficiency and self-reliance of refugees and to improve their socio-economic situations.However, in terms of implementation, economic engagement of refugees has remained to minimum levels. They remain for years unemployed and inactive, struggling with poverty and suffering with all consequences of the unbearable state of limbo, with no way forward and no way backwards. Six interviews have been conducted with experts from five aid and relief organisations as follows; UNHCR, International Federation of Red Cross and Red Crescent Societies (IFRC), Malaysian Social Research Institute (MISR), Islamic Aid Malaysia and (IAM), Islamic Relief Malaysia (IRM). Findings of the interviews indicate to a verity of challenges encountered by NGOs and humanitarian agencies. On top of these challenges in the legal challenge and the absence of the supportive environment in the host countries, followed by the lack of financial resources to support the RMEs and the lack of experienced institutions to cater microfinance and microenterprise for refugees. This study concludes that despite all the challenges, supporting microenterprises for refugees should be given adequate concern due to the changes in refugee trends in terms of the unprecedented number and in terms of the length of the average stay of refugee in exile and due to the successful stories of refugee micro-entrepreneurs when they are encouraged with the supportive business environment in host countries.